OCCAM-Oriented Software Tools - Pakštas, Algirdas; Paketūraite, Danuté; Tamkevičius, Artūras (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1992: Anais do IV Simpósio Brasileiro de Arquitetura de Computadores e Processamento de Alto DesempenhoDO - 10.5753/sbac-pad.1992.22735, 1992)
For many years software engineers have been providing the engineers of other fields with advanced design tools. But the tools used by software designers themselves look quite primitive in comparison. Only CASE-like systems developed during last years can provide reasonable help to software developers. Experimental software development systems ALADDIN/LAMP is oriented to creation of distributed computer control systems (DCCS). Proposed approach to development distributed software configurations (DSCs) is based on the model of virtual distributed software configuration (VDSC) with information-transport ports (ITPs) as interconnecting servers. Transputer networks and OCCAM-written software are often used for creation of DCCS. An approach to ALADDIN/LAMP tools-extention for OCCAM-written DSCs handling is discussed in this paper. Survey of tools is presented (OCCAM-oriented structure editor OSE, OCCAM structure extractor OSX, ALADDIN/OOB translator and deadlock locator and analyser DLA). A comparison with related works is given.